Assessing the agroclimatic potentiality in Indian Sundarbans for crop planning by analyzing rainfall time series data - Ghosh, Argha; Nanda, Manoj Kumar; Sarkar, Debolina; Sarkar, Sukamal; Brahmachari, Koushik; Ray, Krishnendu (Journal of agrometeorology, 2021)
In order to assess the climatological risk in terms of the dry week probabilities and length of the growing period of Indian Sundarbans region for successful crop planning, the present study was conducted using long term rainfall data from 1984 to 2018 received in Gosaba CD (Community Development) block of Indian Sundarbans. The probability of a rainfall events with 25 %, 50%, 75 % probabilities were estimated. Markov Chain model was used to estimate the initial, conditional probabilities of dry and wet weeks along with the probability of two consecutive wet and dry weeks considering 10 mm and 20 mm rainfall thresholds. Length of growing period (LGP) was calculated using Moisture adequacy index computed by the soil water balance method of Thornthwaite and Mather. Weekly rainfall varied from 1.11 mm in 51st Standard Meteorological Week (SMW) with standard deviation of ± 3.41 to 88.49 mm in 29th SMW with standard deviation of ± 58.19.50 % chance of getting more than 20 mm and 10 mm weekly rainfall was observed from 20th (23.37 mm) to 41st SMW (30.64 mm) and 17th (14.63 mm) to 42nd SMW (16.87 mm) respectively. The risk of dry spells was very higher from 42nd to 17th SMW. Average LGP of the study area was 237.4 days with standard deviation of ± 29.88.Probability of a week being stress free growing period and moderately drought period was more than 50 % from 18th to 48th SMW and 49th to 5th SMW respectively. Grass pea, potato with straw mulch and green gram can be included in the rice based cropping system during winter and summer seasons for sustainable intensification of the cropping systems in Indian Sundarbans region.